Copy number variations (CNVs) in Brazilian patients with autism spectrum disorder (ASD) - Claudia Ismania Samogy Costa (2018)
Autism Spectrum Disorder (ASD) is a heterogeneous group of neurodevelopmental disorders that affects about 1% of the worldwide population and has a strong genetic component. Stereotyped behavior and restricted interests, as well as problems of social interaction and communication characterize ASD. Moreover, in 10% of cases, ASD occurs as a secondary condition in addition to a syndrome, such as Phelan-McDermid syndrome (PMS), which is associated with a great clinical variability. Among genetic factors, copy number variations (CNVs) are one of the most important. However, the clinical significance of many CNVs remains nuclear and there is an underrepresentation of small CNVs associated with ASD in the literature. In this context, this project aimed to 1) characterize large and small CNVs in Brazilian patients with ASD using an array-CGH previously customized in our laboratory. 2) Clinically and genetically describe a cohort of Brazilian patients with PMS, as well as to determine the frequency of this syndrome among Brazilian patients with ASD and other neurodevelopmental disorders. In result, we 1) further validated the customized array-CGH, 2) provided additional evidence of association with ASD for 27 candidate genes, 3) described 15 CNVs never reported in the literature in association with this disorder, 4) presented evidence that around 70% of CNVs found in our cohort are not polymorphism of our population and 5) reinforced the idea of shared molecular pathways among different neurodevelopmental disorders. In addition, we described for the first time a Brazilian cohort of patients with PMS and contributed to the molecular and clinical characterization of this syndrome. We also provided additional evidence of genotype-phenotype association with regard to the presence of renal problems and speech status in patients with PMS and estimated the frequency of this syndrome among Brazilian patients with ASD and intellectual disability (syndromic or not). With these results, we hope to contribute to better understand the ASD and PMS etiology, especially in our population